Narrow-distribution low-branching-degree polyethylene wax and preparation method thereof

By using the post-transition metal catalyst of the indigo skeleton and the alkyl aluminoxane cocatalyst for polymerization, the existing polyethylene wax has been solved, and polyethylene wax with narrow molecular weight distribution, low branching degree and excellent performance have been prepared.

CN119569916AActive Publication Date: 2025-03-07PARK BLUE POLYOLEFIN TECH DEV (SHANGHAI) CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411680235.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-07
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing polyethylene wax has a wide molecular weight distribution, many impurities, and poor performance, making it difficult to meet the needs of modern high-end fields.

Method used

The polymerization reaction is carried out using a post-transition metal catalyst with isatin as the skeleton and alkyl aluminoxane as the cocatalyst, and the reaction conditions such as pressure and temperature are controlled to prepare narrow-distribution low-branching polyethylene wax.

Benefits of technology

The obtained polyethylene wax has a narrow molecular weight distribution (PDI <1.5), low branching degree (<50/1000C) and good chemical and physical properties, which meet market demand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148138550000031
    Figure BDA0005148138550000031
  • Figure BDA0005148138550000041
    Figure BDA0005148138550000041
  • Figure BDA0005148138550000042
    Figure BDA0005148138550000042
Patent Text Reader

Abstract

The invention relates to narrow-distribution low-branching-degree polyethylene wax and a preparation method thereof.The preparation method comprises the steps that a solvent, ethylene, a catalyst and a co-catalyst are added into a reaction kettle for a polymerization reaction, after-treatment is conducted after the polymerization reaction is finished, a polyethylene wax product is obtained, and the catalyst is a late transition metal catalyst with isatin as a framework; the cocatalyst comprises alkylaluminoxane, and the molar ratio of the catalyst to the cocatalyst is 1: (100-600). Compared with the prior art, the polyethylene wax with excellent performance is prepared from the late transition metal catalyst with high activity and high thermal stability, and the obtained polyethylene wax is moderate in molecular weight, compact in molecular weight distribution and small in branching degree.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new materials, in particular to a narrow distribution low-branching polyethylene wax and a preparation method thereof. Background Art

[0002] Polyethylene wax (PE-wax) is a polymer material formed by the polymerization of ethylene monomers. It appears as a white granular / flake structure with a molecular weight ranging from 1,000 to 10,000. This lower molecular weight gives PE wax different properties from conventional polyethylene. Polyethylene wax has low viscosity, a high softening point, and high hardness, which makes it widely used in the plastics processing field. Furthermore, PE wax is non-toxic, thermally stable, and has low volatility, which expands its application in extreme environments such as low temperatures and high temperatures. Finally, PE wax has excellent pigment dispersion ability, which not only promotes uniform pigment distribution but also enhances the material's external lubricity and provides excellent internal lubrication, significantly improving the production efficiency of dye processing. Therefore, PE wax has become a high-end material in polyethylene products.

[0003] Currently, the industrial production of polyethylene wax primarily utilizes three methods: byproduct refining, polyethylene cracking, and direct ethylene polymerization. The byproduct refining process involves refining and separating the oligomer components from the previous polyethylene production stage, while the polyethylene cracking process produces polyethylene wax by catalytically degrading high-molecular-weight polyethylene through cracking. The polyethylene wax products obtained by these two methods suffer from a broad molecular weight distribution, high levels of impurities, and poor performance, making them difficult to meet the demands of modern high-end industries. Only polyethylene wax produced through polymerization meets these requirements and meets the modern chemical industry's requirements for efficient atomic utilization and environmentally friendly production.

[0004] Chinese patent CN112745409B discloses a narrow distribution polyethylene wax and a preparation method thereof. This patent obtains polyethylene wax by polymerization reaction using a metallocene catalyst Ph2PN[CH(CH3Ph)]PPh2·CrCl3 or Ph2PN(CHPh2)PPh2·CrCl3. The prepared polyethylene wax has a molecular weight of 500 to 2000 and a PDI of 1.4 to 3.0. This patent uses a metallocene catalyst, which is relatively expensive and requires a large amount of co-catalyst.

[0005] Late transition metal catalysts have unique catalytic properties for ethylene polymerization. Late transition metal catalysts are composed of late transition metals such as Fe, Co, Ni, and Pd coordinated with ligands containing elements such as N, O, and P to form metal organic catalysts. They are prone to β-H elimination reactions to produce low molecular weight polymers. Compared to Ziegler-Natta (ZN) catalysts, which primarily produce high-molecular-weight polyethylene and are expensive metallocene catalysts, they are catalysts with potential for industrial production of polyethylene wax. For example, Chinese patent CN 110092744A discloses a tert-butyl asymmetric diiminopyridine transition metal complex for preparing polyethylene wax. This complex has a single catalytically active center, but the polyethylene wax produced in this patent has a wide molecular weight distribution and requires a large amount of co-catalyst (Al / Fe ≥ 1000), hindering its practical application. Therefore, further research is needed to produce high-quality polyethylene wax products for ethylene polymerization. Summary of the Invention

[0006] The purpose of the present invention is to provide a narrow distribution low branching degree polyethylene wax and a preparation method thereof in order to solve the above problems.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing a polyethylene wax with a narrow distribution and low branching degree, the method comprising: adding a solvent, ethylene, a catalyst and a co-catalyst into a reactor to carry out a polymerization reaction, and performing post-treatment after the polymerization reaction to obtain a polyethylene wax product;

[0009] Wherein, the catalyst is a late transition metal catalyst with indigo as the skeleton;

[0010] The cocatalyst includes an alkylaluminoxane;

[0011] The molar ratio of the catalyst to the co-catalyst is 1:100-600.

[0012] As a preferred technical solution of the present invention, the pressure in the reactor is controlled by ethylene gas, and the pressure in the reactor is controlled at 0.1-10 MPa, preferably 0.1-5 MPa, more preferably 0.1-2 MPa, and even more preferably 0.1-0.5 MPa;

[0013] The temperature in the reactor is controlled at 45-120°C, preferably 60-85°C, and more preferably 60-75°C.

[0014] As a preferred technical solution of the present invention, the solvent is an inert organic solvent, which is a chain alkane, cycloalkane, or benzene aromatic derivative that is liquid at room temperature, has low viscosity, a boiling point not exceeding 120°C, and has low solubility in polyethylene wax, preferably toluene, xylene, or chlorobenzene;

[0015] and / or, the cocatalyst is selected from methylaluminoxane, modified methylaluminoxane, isobutylaluminoxane, and the molar ratio of the catalyst to the cocatalyst is 1:400-600;

[0016] And / or, the catalyst and co-catalyst are diluted with a solvent to form a catalyst dilution solution and then added into the reactor.

[0017] As a preferred technical solution of the present invention, the polymerization reaction is carried out in an anhydrous and oxygen-free environment;

[0018] And / or, the post-treatment is to add acidic methanol to deactivate the catalyst, collect the product and dry it to obtain the polyethylene wax product.

[0019] As a preferred technical solution of the present invention, the catalyst is a nickel metal catalyst with indigo as the skeleton, and its structural formula is:

[0020]

[0021] In the above formula, R 1~ At least one of R5 is an electron-donating group selected from C1-C6 alkyl, C1-C6 alkoxy, aromatic phenyl, R 6~ R8 is selected from H, C1-C6 alkyl, halogen, and X is chlorine or bromine.

[0022] As a preferred technical solution of the present invention, among R1 to R5, at least one of R1, R2, and R5 is selected from a C1-C6 alkyl group, and the others are H. More preferably, R2 is an electron-donating group, and the others are H. As a preferred embodiment, R2 is a methyl group, a methoxy group, or an isopropyl group, and R1, R3, R4, and R5 are H, which is an isatin derivative.

[0023] R6-R8 are each independently selected from H or C1-C6 alkyl. More preferably, at least one of R6, R7, and R8 is an aniline derivative in which the aniline derivative is an electron-donating group, i.e., at least one of R6, R7, and R8 is selected from C1-C6 alkyl, C1-C6 alkoxy, or phenyl. More preferably, R6 is methyl, isopropyl, or methoxy, and / or R7 is methyl, isopropyl, or methoxy, and / or R8 is methyl, isopropyl, or tert-butyl.

[0024] As a preferred technical solution of the present invention, the catalyst is prepared by the following method:

[0025] Under anhydrous and oxygen-free conditions, a diimine ligand with an isatin skeleton and anhydrous nickel salt are added to a reaction vessel containing a solvent, and the mixture is reacted at 15-80° C. for 12-36 hours, wherein the molar ratio of the diimine ligand to the anhydrous nickel salt is 2-3:1. After the reaction is completed, the catalyst solid is obtained by treatment;

[0026] The solvent includes acetonitrile;

[0027] The nickel salts include nickel chloride and nickel bromide.

[0028] As a preferred technical solution of the present invention, the diimine ligand has a structure shown in Formula L:

[0029]

[0030] In formula L, R 1~ At least one of R5 is an electron-donating group selected from C1-C6 alkyl, C1-C6 alkoxy, aromatic phenyl, R 6~ R8 is selected from H, C1-C6 alkyl, halogen.

[0031] As a preferred embodiment of the present invention, the diimine ligand is selected from any one of the following diimine ligand compounds:

[0032]

[0033]

[0034]

[0035] The diimine ligands of formula L are based on isatin and its derivatives. The presence of a six-membered ring and an N-hetero-five-membered ring in isatin provides a certain degree of rigidity, enhancing the thermal stability of late transition metal catalysts when coordinated with metals. Furthermore, the presence of the N-hetero-five-membered ring in isatin, where the nitrogen atom has a higher electronegativity than the carbon atom, and the presence of a lone pair of electrons on the nitrogen atom allows for conjugation with the benzene ring and the diimine structure, further optimizing the catalyst's electronic structure.

[0036] As a preferred technical solution of the present invention, the diimine ligand is prepared by the following method:

[0037] The 1,2-diketone compound and the aromatic amine are dissolved in an organic aprotic polar solvent, a non-oxidizing organic strong acid is added as a catalyst, and the reaction is carried out at 100 to 200° C., preferably 120 to 160° C., for 12 to 36 hours. The solvent is removed from the reaction mixture to obtain a solid product, which is then purified to obtain the product;

[0038] The molar ratio of the 1,2-diketone compound to the aromatic amine is 1:2 to 2.5;

[0039] The organic aprotic polar solvent includes a mixture of toluene and dimethyl sulfoxide;

[0040] The organic strong acid includes p-toluenesulfonic acid.

[0041] A narrow distribution low-branching polyethylene wax prepared by the above-mentioned preparation method, wherein the polyethylene wax has a weight average molecular weight of 3800-8000, a molecular weight distribution between 1.1-1.5, and a branching degree of 10-50 / 1000C.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] The nickel metal catalyst prepared using a novel diimine ligand structure and an indigo carmine backbone exhibits greater rigidity and a more suitable electron cloud density than traditional 1,2-diketone structures, significantly improving the catalyst's catalytic performance and stability. The synthesized late-transition metal catalyst exhibits high catalytic activity over a wide temperature range of 45-120°C. The resulting polyethylene wax exhibits a narrow molecular weight distribution (PDI <1.5) and a low degree of branching (<50 / 1000C), meeting market demand for high-quality polyethylene wax. DETAILED DESCRIPTION

[0044] The present invention will be described in detail below with reference to specific embodiments, but the present invention is by no means limited thereto.

[0045] The inventors have discovered that when a late transition metal catalyst with an indigo carmine skeleton is used to polymerize ethylene to produce polyethylene wax, it can maintain high catalytic activity over a wide range of 45-120°C, particularly high-temperature stability. When used to prepare polyethylene wax, the polyethylene wax product exhibits characteristics such as a narrow molecular weight distribution (PDI <1.5), a low degree of branching (<50 / 1000C), and excellent chemical and physical properties. The inventors speculate that the possible reason is that when indigo carmine is used as the skeleton, the presence of a six-membered ring and an N-hetero-five-membered ring structure in indigo carmine provides a certain degree of rigidity, which can improve the thermal stability of the late transition metal catalyst. The presence of the N-hetero-five-membered ring in indigo carmine has a higher electronegativity than the carbon atom, and the presence of a lone pair of electrons on the N atom can conjugate with the benzene ring and diimine structure, further optimizing the electronic structure of the catalyst. Compared to the traditional 1,2-diketone structure, it has higher rigidity and a suitable electron cloud density, which can improve the catalytic performance and stability of the catalyst.

[0046] Preparation Example: Preparation of late transition metal catalyst with Ni as active center

[0047] The late transition metal catalyst with Ni as the active center is formed by the coordination of a diimine ligand compound and a nickel salt, and its structural formula is:

[0048]

[0049] The catalyst is prepared by the following method:

[0050] Under anhydrous and oxygen-free conditions, a ligand and anhydrous nickel salt (nickel chloride, nickel bromide, preferably nickel chloride) are added to a reaction vessel containing a solvent (e.g., ultra-dry acetonitrile), and the mixture is reacted at 15-80° C. for 12-36 hours, wherein the molar ratio of the ligand to the anhydrous nickel salt is 2-3:1. After the reaction is completed, the catalyst solid is obtained by treatment (after cooling to room temperature, concentrating by reduced pressure evaporation, filtering out the solvent, and washing multiple times with dry n-hexane). The reaction formula is as follows:

[0051]

[0052] Wherein, the diimine ligand is prepared by the following method:

[0053] A 1,2-diketone compound and an aromatic amine (at a molar ratio of 1:2 to 2.5) are dissolved in an organic aprotic polar solvent (e.g., a mixture of toluene and DMSO), and a non-oxidizing organic strong acid (e.g., p-toluenesulfonic acid) is added as a catalyst. The mixture is reacted at 100 to 200° C., preferably 120 to 160° C., for 12 to 36 hours. The solvent is removed from the reaction mixture (e.g., by rotary evaporation), and the obtained solid product is purified (e.g., by recrystallization) to obtain the ligand. The reaction formula is as follows:

[0054]

[0055] Taking L1 as an example, the synthesis steps are as follows:

[0056]

[0057] Add about 100 ml of mixed solution (V 甲苯 :V DMSO =9:1) as a solvent, followed by the addition of an isatin derivative (R1-methyl substituted isatin, 10 mmol) and an aniline derivative (aniline, 21 mmol), the mixture being uniformly mixed, and then catalytic p-toluenesulfonic acid (10 μmol) was added, the mixture was refluxed at 120° C. with water separation for 24 hours, and the mixture after reaction was rotary evaporated to remove the solvent, and the resulting solid was recrystallized to obtain ligand L1.

[0058] Ligands L1 to L10 were prepared according to the above method, see Table 1 for details.

[0059] The specific information of the reagents used is as follows (taking R1-methyl substituted Dianhong as an example, it means that R1 is methyl and the other groups are H).

[0060] R1-Methyl substituted Dian Hong (CAS: 2058-74-4 Sigma-Aldrich)

[0061] R2-methyl substituted Dianhong (CAS: 1127-59-9 Leyan Reagent)

[0062] R5-Methyl substituted Dianhong (CAS:1127-59-9Mecklin)

[0063] R2-isopropyl substituted isatin (CAS: 66232-59-5)

[0064] Sodium sulfate (CAS:7757-82-6Sigma-Aldrich)

[0065] Chloral hydrate (CAS: 302-17-0 Sigma-Aldrich)

[0066] Hydroxylamine sulfate (CAS:10039-54-0Sigma-Aldrich)

[0067] Concentrated hydrochloric acid (CAS:7647-01-0Sigma-Aldrich)

[0068] m-Isopropylaniline (CAS: 108-44-1Aladdin)

[0069] R6-Methyl substituted aniline (CAS:87-62-7Sigma-Aldrich)

[0070] R6-Bromo-substituted aniline (CAS: 608-3-0 Sigma-Aldrich)

[0071] R6-Isopropyl substituted aniline (CAS: 24544-04-5 Sigma-Aldrich) R7-Methyl substituted aniline (CAS: 108-69-0 Sigma-Aldrich)

[0072] R8-Methyl substituted aniline (CAS: 106-49-0 Sigma-Aldrich)

[0073] 2,6-Diacetylpyridine (CAS:1129-30-2Sigma-Aldrich)

[0074] Salicylaldehyde (CAS:90-02-8Sigma-Aldrich)

[0075] Bis(triphenylphosphine)nickel(II) chloride (CAS:14264-16-5Sigma-Aldrich) Tetrahydrofuran (CAS:109-99-9Sigma-Aldrich)

[0076] n-Hexane (CAS:110-54-3Sigma-Aldrich)

[0077] Diethyl ether (CAS: 60-29-7Aladdin)

[0078] Concentrated sulfuric acid (CAS:7664-39-9Aladdin)

[0079] Toluene (CAS: 108-88-3Sigma-Aldrich)

[0080] Dimethyl sulfoxide (CAS: 67-68-5 Sigma-Aldrich)

[0081] Ethanol (CAS: 64-17-5 Sigma-Aldrich)

[0082] Acetonitrile (CAS:75-05-8Sigma-Aldrich)

[0083] p-Toluenesulfonic acid (CAS: 6192-52-5 Sigma-Aldrich)

[0084] Unless otherwise specified, all solvents involved in the present invention need to be treated to remove water.

[0085] Table 1 Raw materials for preparation of ligands L1 to L10

[0086]

[0087]

[0088]

[0089] Ligand L1

[0090] In a 250ml three-necked flask, add 100ml of mixed organic solvent (V 甲苯 :V DMSO =9:1), then R1-methyl-substituted Dian Hong (10 mmol) and aniline (21 mmol) were added to the flask and mixed evenly. A catalytic equivalent of p-toluenesulfonic acid (approximately 10 μmol) was then added and refluxed at 120°C for 24 hours. After the reaction, the solvent was removed by distillation under reduced pressure, and the product was recrystallized from ethanol to obtain ligand L1 with a final yield of 87%. ( 1 H 300MHz, DMSO): 7.62-6.81 (m, 14H, Ar-H), 3.55 (s, 3H, CH3). C 21 H 17 N3: Calculated values ​​(%): C, 81.00; H, 5.50; N, 13.49. Found (%): C, 81.24; H, 5.52; N, 13.41.

[0091] Ligand L2

[0092] In a 250ml three-necked flask, add 100ml of mixed organic solvent (V 甲苯 :V DMSO =9:1), then R2-methyl-substituted Dian Hong (10 mmol) and aniline (21 mmol) were added to the flask and mixed evenly. A catalytic equivalent of p-toluenesulfonic acid (approximately 10 μmol) was then added and the mixture was refluxed at 120°C for 24 hours. After the reaction, the solvent was removed by distillation under reduced pressure, and the product was recrystallized from ethanol to obtain ligand L2 with a final yield of 81%. ( 1 H 300MHz, DMSO): 11.11 (s, 1H, NH), 7.55-6.82 (m, 13H, Ar-H), 2.75-1.88 (m, 3H, CH3). C 21 H 17 N3: Calculated values ​​(%): C, 81.00; H, 5.50; N, 13.49. Found (%): C, 81.15; H, 5.54; N, 13.47.

[0093] Ligand L3

[0094] In a 250ml three-necked flask, add 100ml of mixed organic solvent (V 甲苯 :V DMSO =9:1), then R5-methyl-substituted Dianhong (10 mmol) and aniline (21 mmol) were added to the flask and mixed evenly. A catalytic equivalent of p-toluenesulfonic acid (approximately 10 μmol) was then added and refluxed at 120°C for 24 hours. After the reaction, the solvent was removed by distillation under reduced pressure, and the product was recrystallized and purified using ethanol solution to obtain ligand L3 with a final yield of 85%. ( 1 H 300MHz, DMSO): 11.24 (s, 1H, NH), 7.45-6.02 (m, 13H, Ar-H), 2.83-1.95 (m, 3H, CH3). C 21 H 17 N3: Calculated values ​​(%): C, 81.00; H, 5.50; N, 13.49. Found (%): C, 81.07; H, 5.62; N, 13.53.

[0095] Ligand L4

[0096] In a 250ml three-necked flask, add 100ml of mixed organic solvent (V 甲苯 :V DMSO=9:1), then R2-isomethyl substituted Dian Hong (10 mmol) and aniline (21 mmol) were added to the flask and mixed evenly. Then, a catalytic equivalent of p-toluenesulfonic acid (approximately 10 μmol) was added and the mixture was refluxed at 120°C for 24 hours. After the reaction, the solvent was removed by distillation under reduced pressure, and the product was recrystallized from ethanol to obtain ligand L4 with a final yield of 77%. ( 1 H 300MHz, DMSO): 10.96 (s, 1H, NH), 7.56-6.90 (m, 13H, Ar-H), 3.05-2.08 (m, 7H, CH (CH3) 2). C 23 H 21 N3: Calculated values ​​(%): C, 81.38; H, 6.24; N, 12.38. Found (%): C, 81.46; H, 6.39; N, 12.40.

[0097] Ligand L5

[0098] In a 250ml three-necked flask, add 100ml of mixed organic solvent (V 甲苯 :V DMSO =9:1), then R2-tert-butyl substituted Dian Hong (10 mmol) and aniline (21 mmol) were added to the flask and mixed evenly. A catalytic equivalent of p-toluenesulfonic acid (approximately 10 μmol) was then added and refluxed at 120°C for 24 hours. After the reaction, the solvent was removed by distillation under reduced pressure, and the product was recrystallized from ethanol to obtain ligand L5 with a final yield of 72%. ( 1 H 300MHz, DMSO): 11.23(s,1H,NH), 7.61-6.75(m,13H,Ar-H), 2.95-1.05(m,9H,C(CH3)3). C 24 H 23 N3: Calculated values ​​(%): C, 81.55; H, 6.56; N, 11.89. Experimen-tal values ​​(%): C, 81.58; H, 6.59; N, 11.90.

[0099] Ligand L6

[0100] In a 250ml three-necked flask, add 100ml of mixed organic solvent (V 甲苯 :V DMSO=9:1), then R2-isopropyl-substituted Dianhong (10 mmol) and R6-methyl-substituted aniline (21 mmol) were added to the flask and mixed evenly. A catalytic equivalent of p-toluenesulfonic acid (approximately 10 μmol) was then added, and the mixture was refluxed at 120°C for 24 hours. After the reaction, the solvent was removed by distillation under reduced pressure, and the product was recrystallized from ethanol to obtain ligand L6 with a final yield of 82%. ( 1 H 300MHz, DMSO): 11.40(s,1H,NH), 7.44-6.92(m,9H,Ar-H), 3.11-2.38(m,19H,CH(CH3)2). C 27 H 29 N3: Calculated values ​​(%): C, 81.99; H, 7.39; N, 10.62. Experimen-tal values ​​(%): C, 82.06; H, 7.49; N, 10.57.

[0101] Ligand L7

[0102] In a 250ml three-necked flask, add 100ml of mixed organic solvent (V 甲苯 :V DMSO =9:1), then R2-isopropyl-substituted Dianhong (10 mmol) and R6-bromo-substituted aniline (21 mmol) were added to the flask and mixed evenly. A catalytic equivalent of p-toluenesulfonic acid (approximately 10 μmol) was then added, and the mixture was refluxed at 120°C for 24 hours. After the reaction, the solvent was removed by distillation under reduced pressure, and the product was recrystallized from an ethanol solution to obtain ligand L7 with a final yield of 80%. ( 1 H 300MHz, DMSO): 11.27(s,1H,NH), 7.60-6.81(m,9H,Ar-H), 3.31-1.48(m,7H,CH(CH3)2). C 23 H 17 N3Br4: Elemental analysis calculated (%): C, 42.17; H, 2.62; N, 6.42; Br, 48.79. Experiential determination (%): C, 42.16; H, 2.69; N, 6.47; Br, 48.77.

[0103] Ligand L8

[0104] In a 250ml three-necked flask, add 100ml of mixed organic solvent (V 甲苯 :V DMSO=9:1), then R2-isopropyl-substituted isatin (10 mmol) and R6-isopropyl-substituted aniline (21 mmol) were added to the flask and mixed evenly. A catalytic equivalent of p-toluenesulfonic acid (approximately 10 μmol) was then added, and the mixture was refluxed at 120°C for 24 hours. After the reaction, the solvent was removed by distillation under reduced pressure, and the product was recrystallized from ethanol to obtain ligand L8 with a final yield of 77%. ( 1 H 300MHz, DMSO): 11.15(s,1H,NH), 7.77-6.92(m,9H,Ar-H), 3.19-1.35(m,35H,CH(CH3)2). C 35 H 45 N3: Calculated values ​​(%): C, 82.79; H, 8.93; N, 8.28. Experimen-tal values ​​(%): C, 82.86; H, 8.97; N, 8.47.

[0105] Ligand L9

[0106] In a 250ml three-necked flask, add 100ml of mixed organic solvent (V 甲苯 :V DMSO =9:1), then R2-isopropyl-substituted Dianhong (10 mmol) and R7-methyl-substituted aniline (21 mmol) were added to the flask and mixed evenly. A catalytic equivalent of p-toluenesulfonic acid (approximately 10 μmol) was then added, and the mixture was refluxed at 120°C for 24 hours. After the reaction, the solvent was removed by distillation under reduced pressure, and the product was recrystallized from an ethanol solution to obtain ligand L9 with a final yield of 72%. ( 1 H 300MHz, DMSO): 11.29(s,1H,NH), 7.45-6.93(m,9H,Ar-H), 3.34-1.55(m,19H,CH(CH3)2). C 27 H 29 N3: Calculated values ​​(%): C, 81.99; H, 7.39; N, 10.62. Experimen tal values ​​(%): C, 82.02; H, 7.47; N, 10.66.

[0107] Ligand L10

[0108] In a 250ml three-necked flask, add 100ml of mixed organic solvent (V 甲苯 :V DMSO=9:1), then R2-isopropyl-substituted Dianhong (10 mmol) and R8-methyl-substituted aniline (21 mmol) were added to the flask and mixed evenly. A catalytic equivalent of p-toluenesulfonic acid (approximately 10 μmol) was then added, and the mixture was refluxed at 120°C for 24 hours. After the reaction, the solvent was removed by distillation under reduced pressure, and the product was recrystallized from ethanol to obtain ligand L10 with a final yield of 89%. ( 1 H 300MHz, DMSO): 11.50(s,1H,NH), 7.52-6.88(m,11H,Ar-H), 3.16-1.37(m,13H,CH3 CH(CH3)2). C 25 H 25 N3: Calculated values ​​(%): C, 81.71; H, 6.96; N, 11.43. Experimen-tal values ​​(%): C, 81.78; H, 7.02; N, 11.59.

[0109] Preparation of catalysts C1 to C10

[0110] The above-obtained ligands are coordinated with NiCl2 respectively, and the reaction equation is as follows:

[0111]

[0112] The specific steps are as follows: under anhydrous and oxygen-free conditions, about 100 ml of ultra-dry acetonitrile is added to a three-necked flask, and ligands L1 to L10 (8.4 mmol) and anhydrous NiC12 (4 mmol) are added respectively. The reaction temperature is controlled at 55° C. and the reaction time is 24 hours. After the reaction is completed, the mixture is cooled to room temperature, concentrated by evaporation, the solvent is filtered out, and the mixture is washed multiple times with dry n-hexane and dried to obtain catalysts C1 to C10.

[0113] Preparation of catalysts C1'-C3'

[0114] As a comparison, the present invention prepared catalysts C1'-C3'.

[0115] Catalyst C1'

[0116] Preparation of ligand L1': In a 250ml three-necked flask, 2,3-butanedione (10 mmol) and aniline (22 mmol) were dissolved in 100ml of toluene. Catalytic p-toluenesulfonic acid (approximately 10 μmol) was added. The mixture was refluxed at 100°C with water for 24 hours. After the reaction, the toluene solvent was removed by vacuum distillation, and the solid product was recrystallized from hot ethanol. The final yield was 86%.

[0117]

[0118] Synthesis of Catalyst C1': A single-necked flask was charged with the synthesized ligand (5 mmol) and anhydrous NiCl2 (11 mmol), followed by anhydrous acetonitrile. The mixture was then evacuated with nitrogen three times and refluxed at 55°C for 24 hours. After completion of the reaction, the mixture was cooled to room temperature, concentrated under reduced pressure, filtered, and washed with n-hexane to obtain a solid. The final yield was 77%. The reaction equation is as follows:

[0119]

[0120] Catalyst C2'

[0121] Preparation of ligand L2': Add 3 mmol of 2,6-diacetylpyridine and 3.4 mmol of aniline to a 150 ml three-necked flask, then add 50 ml of toluene, stir and heat under reflux. After half an hour of reaction, add a catalytic amount of p-toluenesulfonic acid (about 10 μmol) and continue the reaction for 12 hours. Cool to room temperature and remove the solvent by rotary evaporation. Then, perform column chromatography on a basic alumina column (eluent V 石油醚 :V 乙酸乙酯 =100:1) to finally obtain the pyridine diimine ligand with a yield of 48%.

[0122]

[0123] Synthesis of Catalyst C2': The pyridine diimine ligand (1 mmol) prepared above and FeCl2·4H2O (1.2 mmol) were added to a 50 ml single-necked flask. The flask was then pumped with nitrogen three times to create a water- and oxygen-free environment. Redistilled anhydrous ethanol was then added and stirred at room temperature for 12 hours. The mixture was filtered and washed with diethyl ether. The final yield of the product was 95%.

[0124]

[0125] Catalyst C3'

[0126] Preparation of Ligand L3': Under argon, salicylaldehyde (0.2 mol) and 60 ml of anhydrous ethanol were added to a 250 ml three-necked flask. Aniline (0.02 mol) was then added to the flask using a constant pressure dropping funnel, followed by formic acid (0.5 ml). The mixture was heated to 80°C and allowed to react for 2 h. After cooling to room temperature, the mixture was evaporated under reduced pressure and the product precipitated on cooling. The final yield of the product was 88%.

[0127]

[0128] The synthesis steps for R2-isopropyl-substituted Dianhong are as follows: A mixture of sodium sulfate (0.915 mol), distilled water (120 ml), chloral hydrate (0.109 mol), hydroxylamine sulfate (0.079 mol), 8.6 ml of concentrated hydrochloric acid (37%), and m-isopropylaniline (0.1 mol) dissolved in 60 ml of distilled water is gradually heated to 70°C. 100 ml of ethanol is then added, and the mixture is heated to reflux. After a 1-hour reaction, the mixture is poured into ice water, and the solid 3-isopropylisonitrosoacetanilide is collected by filtration and washed with water. The final yield of 3-isopropylisonitrosoacetanilide is 81%. Subsequently, 3-isopropylisonitrosoacetanilide (17 mmol) is slowly added to concentrated sulfuric acid (9 ml) at room temperature under magnetic stirring. After a 15-minute reaction, the reaction mixture is poured into crushed ice and collected by filtration to obtain a mixture of products 1 and 2. Product 2 was subsequently purified using a forced crystallization method: a mixture of products 1 and 2 was dissolved in a minimal amount of DMSO. The DMSO was slowly added dropwise to a large amount of n-hexane solution. Due to the difference in polarity, solid product 1 precipitated. Filtration was repeated several times, and finally, product 2 dissolved in n-hexane was rotary evaporated and washed with distilled water. The final yield of R2-isopropyl-substituted isatin was 45%.

[0129]

[0130] Synthesis of catalyst C3': 40 ml of freshly distilled THF and NaH (4 mmol) were added to a 100 ml three-necked flask and the mixture was evacuated with nitrogen three times. The salicylaldimine ligand was then slowly added dropwise to the flask using a constant pressure dropping funnel and stirred at room temperature for 3 h. Unreacted NaH was removed by filtration. Finally, 40 ml of toluene and (Ph3)2PhNiCl (1.5 mmol) were added and stirred at room temperature for 12 h. The filtrate was concentrated and n-hexane solution was slowly added until crystals precipitated. Finally, the product was recrystallized from toluene and n-hexane solution with a final product yield of 70%.

[0131]

[0132] [Example] Preparation of polyethylene wax

[0133] The preparation method of polyethylene wax is specifically as follows:

[0134] A 250ml stainless steel reactor was heated at 150°C under vacuum for 2 hours, then cooled to ambient temperature. The reactor was then pressurized to 1.2 atm with ethylene, vented, and re-pressurized with ethylene three times to ensure a full ethylene atmosphere. The cocatalyst MAO (1 mmol) was then dissolved in approximately 100ml of dry toluene and injected into the reactor. Stirring was continued under 1.2 atm of ethylene pressure for 5 minutes. Finally, 50ml of a toluene dilution of catalysts C1-C10 (containing approximately 2 μmol of catalyst) was added to the reactor via syringe and stirred uniformly. Gaseous ethylene was continuously added throughout the reaction, maintaining an ethylene pressure of 10 atm. The reaction temperature was maintained between 45 and 120°C during polymerization experiments. The polymerization process was complete after 1 hour. For post-treatment, acidic methanol (ethanol / hydrochloric acid, 95:5 by weight) was added to deactivate the catalyst. The resulting precipitated polymer was collected, separated by rotary evaporation, and dried in vacuo at 40°C to a constant weight to yield polyethylene wax.

[0135] In the same manner as above, ethylene polymerization experiments were carried out using catalysts C1' to C3' as catalysts.

[0136] The catalytic activity of each catalyst was tested at different reaction temperatures. The catalytic activity was calculated based on the yield of the polyethylene wax sample, expressed as g polyethylene wax / (mol catalyst × h). The specific results are shown in Table 2.

[0137] Table 2 Catalytic activity of different catalysts at different temperatures (10 6 g PE / mol cat h)

[0138]

[0139]

[0140] Note: “--” in Table 2 means not performed.

[0141] As shown in Table 2, catalysts C1 to C10 have high catalytic activity at 45°C-120°C, and the activity of catalysts with electron-donating groups is better than that of catalysts with electron-withdrawing groups (catalyst C7). From the perspective of catalyst structure, when the substituents on R2 and R6 have certain steric hindrance effects and electron-donating effects, the two interact with each other. For example, catalyst C8 exhibits the best catalytic activity, with a catalytic activity of 11.45×10- 6 gPE / g cat h, at a high temperature of 120 ° C, it still has a value of 6.35×10 6 The catalytic activity of gPE / gcat h far exceeds that of other non-isatin framework late transition metal catalysts.

[0142] Example 1

[0143] Polyethylene wax was prepared as follows: A 250ml stainless steel reactor was heated under vacuum at 150°C for 2 hours, then cooled to ambient temperature. The reactor was then pressurized to 1.2 atm with ethylene, vented, and re-pressurized with ethylene. This process was repeated three times to ensure a full ethylene atmosphere. The cocatalyst MAO (1 mmol) was dissolved in approximately 100ml of dry toluene and injected into the reactor. Stirring was continued under 1.2 atm of ethylene pressure for 5 minutes. Finally, 50ml of a toluene dilution of catalyst C1 (containing approximately 2 μmol of catalyst) was added to the reactor via syringe and stirred uniformly. Gaseous ethylene was continuously added throughout the reaction, maintaining an ethylene pressure of 10 atm. The reaction temperature was maintained at 45°C during the polymerization experiment. After 2 hours of reaction, polymerization was complete. The catalyst was deactivated by adding acidic methanol (95:5 ethanol / hydrochloric acid by weight). The resulting precipitated polymer was collected, separated by rotary evaporation, and dried under vacuum at 40°C to a constant weight, yielding polyethylene wax sample E1.

[0144] Example 2

[0145] The same method as in Example 1 was used, except that catalyst C2 was used for polymerization at 60° C. to obtain polyethylene wax sample E2.

[0146] Example 3

[0147] The same method as in Example 1 was used, except that catalyst C3 was used for polymerization at 75° C. to obtain polyethylene wax sample E3.

[0148] Example 4

[0149] The same method as in Example 1 was used, except that catalyst C5 was used for polymerization at 60° C. to obtain polyethylene wax sample E4.

[0150] Example 5

[0151] The same method as in Example 1 was used, except that catalyst C6 was used for polymerization at 75° C. to obtain polyethylene wax sample E5.

[0152] Example 6

[0153] The same method as in Example 1 was used, except that catalyst C7 was used for polymerization at 60° C. to obtain polyethylene wax sample E6.

[0154] Example 7

[0155] The same method as in Example 1 was used, except that catalyst C8 was used for polymerization at 75° C. to obtain polyethylene wax sample E7.

[0156] Example 8

[0157] The same method as in Example 1 was used, except that catalyst C10 was used for polymerization at 45° C. to obtain polyethylene wax sample E8.

[0158] [Comparative Example]

[0159] Comparative Example 1

[0160] The same method as in Example 1 was used, except that the catalyst C1' was used for polymerization at 60°C to obtain a polyethylene wax sample E1'.

[0161] Comparative Example 2

[0162] The same method as in Example 1 was used, except that the catalyst C2' was used for polymerization at 45° C. to obtain a polyethylene wax sample E2'.

[0163] Comparative Example 3

[0164] The same method as in Example 1 was used, except that the catalyst C3' was used for polymerization at 75° C. to obtain a polyethylene wax sample E3'.

[0165] Comparative Example 4

[0166] The same method as in Example 1 was used, except that the polymerization was carried out at 75° C. using catalyst C4′, which was a metallocene catalyst titanocene dichloride, to obtain polyethylene wax sample E4′.

[0167] Comparative Example 5

[0168] Polyethylene wax was prepared by free radical initiation. The specific preparation method was as follows: a 250ml stainless steel reactor was heated in a vacuum at 150°C for 2 hours, then cooled to ambient temperature. The reactor was then pressurized to 1.2 atm with ethylene, vented, and re-pressurized with ethylene. This process was repeated three times to ensure a full ethylene atmosphere. 5 μmol of the initiator dibenzoyl peroxide (BPO) was dissolved in approximately 100 ml of dry toluene and injected into the reactor. Gaseous ethylene was continuously added throughout the reaction, maintaining an ethylene pressure of 100 atm. The reaction temperature was maintained at 85°C during the polymerization experiment. The polymerization process was complete after 2 hours. The resulting precipitated polymer was collected, separated by rotary evaporation, and dried in a vacuum at 40°C to a constant weight, yielding polyethylene wax sample E5'.

[0169]

Polyethylene wax sample test

[0170] The performance of polyethylene wax samples E1 to E8 and samples E1' to E5' were tested using the following methods:

[0171] (1) Molecular weight determination

[0172] Molecular weight determination includes weight-average molecular weight (Mw) and number-average molecular weight (Mn): determined by gel permeation chromatography (GPC) in accordance with GB / T 27843-2011, "Polymers in Chemicals - Determination of Low Molecular Weight Content - Gel Permeation Chromatography (GPC)." The molecular weight distribution index (PDI) of polyethylene wax is determined by the ratio of the measured weight-average molecular weight to the number-average molecular weight.

[0173] (2) Determination of branching degree

[0174] The degree of branching of polyethylene wax was calculated by H NMR spectrum.

[0175] (3) Drop melting point viscosity measurement

[0176] The drop melting point is determined in accordance with GB / T 8026-2014 “Determination of drop melting point of petroleum waxes and petroleum fats”.

[0177] The specific test results are shown in Table 3.

[0178] Table 3 Polyethylene wax sample property determination

[0179]

[0180]

[0181] As shown in Table 3, the polyethylene wax prepared in the present invention has a weight-average molecular weight of 3800-8000, a narrow molecular weight distribution of 1.12-1.48, and a branching degree of 10-50 / 1000°C (less than 50 / 1000°C, low branching), making it a high-performance polyethylene wax. Compared to polyethylene waxes produced using other types of late transition metal catalysts, it has a moderate molecular weight, a tight molecular weight distribution, and a low degree of branching. Its overall performance is superior to that of the comparative example and can meet market demand. In the comparative example, sample E4' is produced using the metallocene catalyst titanocene dichloride, which has high catalyst cost, poor high temperature resistance, and poor polar solvent resistance. Samples E1', E2', E3', and E5' also have high molecular weight distribution indices and poor product consistency.

[0182] The above description of the embodiments is intended to facilitate understanding and use of the invention by those skilled in the art. It will be apparent that those skilled in the art can readily make various modifications to these embodiments and apply the general principles described herein to other embodiments without requiring inventive effort. Therefore, the present invention is not limited to the above-described embodiments. Improvements and modifications made by those skilled in the art based on the disclosure of the present invention, without departing from the scope of the present invention, should be within the scope of protection of the present invention.

Claims

1. A method for preparing a narrow distribution low-branching degree polyethylene wax, characterized in that: Adding solvent, ethylene, catalyst and co-catalyst into the reaction kettle to carry out polymerization reaction, and after the polymerization reaction is completed, post-treatment is carried out to obtain a polyethylene wax product; Wherein, the catalyst is a late transition metal catalyst with indigo as the skeleton; The cocatalyst comprises an alkylaluminoxane; The molar ratio of the catalyst to the co-catalyst is 1:100-600.

2. The method for preparing a narrow distribution low branching degree polyethylene wax according to claim 1, characterized in that: The pressure in the reactor is controlled by ethylene gas, and the pressure in the reactor is controlled at 0.1-10 MPa, preferably 0.1-5 MPa; The temperature in the reactor is controlled at 45-120°C, preferably 60-85°C.

3. The method for preparing a narrow distribution low branching degree polyethylene wax according to claim 1, characterized in that: The solvent is an inert organic solvent, which is a chain alkane, cycloalkane, or benzene aromatic derivative that is liquid at room temperature, has low viscosity, a boiling point not exceeding 120° C., and has low solubility in polyethylene wax; And / or, the cocatalyst is selected from methylaluminoxane, modified methylaluminoxane, isobutylaluminoxane, and the molar ratio of the catalyst to the cocatalyst is 1:400-600; And / or, the catalyst and the co-catalyst are diluted with a solvent to form a catalyst diluent and then added into the reaction kettle.

4. The method for preparing a narrow distribution low branching degree polyethylene wax according to claim 1, characterized in that: The polymerization reaction is carried out in an environment without water or oxygen; And / or, the post-treatment is to add acidic methanol to deactivate the catalyst, collect the product and dry it to obtain the polyethylene wax product.

5. The method for preparing a narrow distribution low branching degree polyethylene wax according to claim 1, characterized in that: The catalyst is a nickel metal catalyst with indigo as the skeleton, and its structural formula is: In the formula, R 1~ At least one R5 is an electron-donating group selected from C1-C6 alkyl, C1-C6 alkoxy, aromatic phenyl, R 6~ R8 is selected from H, C1-C6 alkyl, halogen, and X is chlorine or bromine.

6. The method for preparing a narrow distribution low branching degree polyethylene wax according to claim 5, characterized in that: Among R1 to R5, at least one of R1, R2 and R5 is selected from C1-C6 alkyl, and the rest are H; R6 to R8 are each independently selected from H or C1-C6 alkyl.

7. The method for preparing a narrow distribution low branching degree polyethylene wax according to claim 5, characterized in that: The catalyst is prepared by the following method: Under anhydrous and oxygen-free conditions, a diimine ligand with indigo carmine as a skeleton and anhydrous nickel salt are added to a reaction vessel into which a solvent is added, and the reaction is carried out at 15 to 80° C. for 12 to 36 hours, wherein the molar ratio of the diimine ligand to the anhydrous nickel salt is 2 to 3:1, and after the reaction is completed, a catalyst solid is obtained by treatment; The solvent includes acetonitrile; The nickel salts include nickel chloride and nickel bromide.

8. The method for preparing a narrow distribution low branching degree polyethylene wax according to claim 7, characterized in that: The diimine ligand has a structure shown in Formula L: In formula L, R 1~ At least one of R5 is an electron donating group selected from C1-C6 alkyl, C1-C6 alkoxy, aromatic phenyl, R 6~ R8 is selected from H, C1-C6 alkyl, halogen.

9. The method for preparing a narrow distribution low-branching degree polyethylene wax according to claim 8, characterized in that: The diimine ligand is prepared by the following method: 1,2-diketone compounds and aromatic amines are dissolved in an organic non-protonic polar solvent, a non-oxidizing organic strong acid is added as a catalyst, and the reaction is carried out at 100-200° C. for 12-36 hours. The solvent is removed from the mixture after the reaction to obtain a solid product, which is obtained after purification; The molar ratio of the 1,2-diketone compound to the aromatic amine is 1:2 to 2.5; The organic aprotic polar solvent includes a mixture of toluene and dimethyl sulfoxide; The organic strong acid includes p-toluenesulfonic acid.

10. A narrow distribution low branching degree polyethylene wax prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The weight average molecular weight of the polyethylene wax is 3800-8000, the molecular weight distribution is between 1.1-1.5, and the branching degree is 10-50 / 1000C.

Citation Information

Patent Citations

  • A narrow-distribution polyethylene wax and its preparation method

    CN112745409B

  • Diketinimatonickel catalyst and application of same to preparation of branched polyethylene

    CN106478848A

  • A class of high thermal stability coordination compounds containing tert-butyl asymmetric diimine pyridine, preparation method and applications thereof

    CN110092744A

  • Alpha-diimine nickel complex, metal catalyst, branched polyethylene wax and preparation method and application thereof

    CN110511251A

  • Process for preparation of indole-3-carboxylic acid derivatives

    CN118265698A